AC electrical conductivity of Cr-doped polyaniline/poly(vinyl alcohol) blends - Soares,D.A.W. (2004)
Polyaniline (PANI) and their charge transfer complexes are engineering materials that continue to attract considerable attention from engineers due to their unique electrochemical behavior, environmental stability and high degree of processability. Extensive works on the preparation of electrically conductive PANI blends containing a polymeric matrix having desirable physical and good mechanical characteristics have pointed as a promising route to overcome the PANI intractabilities. This paper reports the electrical properties of the dichromated PANI/poly(vinyl alcohol) (PANI:Cr3+/PVA) blends. Doped polyaniline powder in the emeraldine base form was synthesized by the classical chemical oxidation of aniline with ammonium persulfate as the oxidant in the presence of chromium (Cr3+). The SEM (Phillips XL 30) was used to understand the changes occurring in the conductivity to a microstructure level. The distribution of PANI:Cr3+ (50% w/w) in the host polymer (PVA) show some tendency to occur in "flocculated structures". The samples were cut into circular shapes to form films about 500 microns thick. Electrical contacts were made by sputtering gold over sample surfaces. We have carried out impedance spectroscopy measurements in the range of 20Hz to 1MHz. Measurements carried at 100K and 250K indicates that thermally activated carrier process between PANI:Cr3+ grains in the PANI:Cr3+/PVA blend sample are responsible for its high temperature conductivity.